PENGARUH STRATEGI PEMBELAJARAN DAN MOTIVASI BELAJAR MAHASISWA TERHADAP HASIL BELAJAR MATA KULIAH PROSES PRODUKSI PADA PROGRAM STUDI TEKNIK MESIN FAKULTAS TEKNIK UNIVERSITAS DARMA AGUNG MEDAN - Hodmiantua Sitanggang; Efendi Napitupulu; Sofyan Matondang (JURNAL PROINTEGRITA, 2021)
This research aims at analyzing the influence of learning strategy and motivation to learn students on the outcome of the production process in mechanical engineering study program of Darma Agung University of Medan. The research method used is a double linear regression analysis, with a sample number of 59 respondents. Research instruments are tested with validity tests and reliability tests. Test prerequisite analysis is done by normality test, multicolinearity test and heteroskedaticity test. The hypothesis test is performed with a partial test (t-test), simultaneous test (F-test) and a coefficient of determination test (R2 test). Analysis results obtained multiple linear regression equations Y = 16.168 + 1.366 (X1) + 0.454 (X2). Based on the hypothesis test acquired results: Learning strategy is positively and significantly influential about the outcome of the production process course; Motivation to learn positive and significant effect on learning outcomes of production process and learning strategy and learning motivation simultaneously positively and significantly affect the results of learning course production process. In order to improve student learning outcomes in the production process, the lecturers should be able to improve the learning strategy and learning motivation for the students taking the course.